Highly efficient white fluorescence/phosphorescence hybrid organic light emitting devices based on an efficient hole-transporting blue emitter. (April 2015) - Du, Xiaoyang; Huang, Yun; Tao, Silu; Yang, Xiaoxia; Ding, Xulin; Zhang, Xiaohong
Abstract: 4, 4'-di-(1-pyrenyl)-4''-[2-(9, 9'-dimethylfluorene)]triphenylamine was proved to be a hole-transporting blue emitter with a hole-mobility of 6.40 × 10 −5  cm 2  V −1  s −1 . A blue organic light emitting device using the compound as a fluorescent dopant shows a maximum luminance efficiency of 5.8 cd A −1 (5.2 lm W −1, 4.5%) with Commission Internationale de L'Eclairage coordinates of x = 0.16, y = 0.18. Fluorescence/phosphorescence hybrid white device employed the compound and Ir(2-phq)3 respectively as blue and orange emitter has been fabricated, which shows a warm white emission with a maximum efficiency of 16.8 cd A −1 (16.1 lm W −1 ). Moreover, high efficiency three-color fluorescence/phosphorescence hybrid white organic light emitting device using the compound as blue fluorescent emitter combining with phosphorescent yellowish-green emitter (Ir(ppy)2 bop) and red emitter (Ir(piq)3 ) has been achieved. The white device shows a maximum efficiency of 42.5 cd A −1 (38.2 lm W −1, 15.5%), with a Color-Rendering Index of 76, which is among the best results for previously reported fluorescence/phosphorescence white devices. Highlights: Efficient blue OLEDs have been fabricated using a hole transporting blue emitter. Two-color white OLED has been fabricated and shows a warm white emission. Efficient three-color white OLEDs have been achieved with high performance.